2020
DOI: 10.18632/aging.102750
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal overexpression of G9a in melanoma cells promotes cancer progression via upregulation of the Notch1 signaling pathway

Abstract: Malignant melanoma is a type of very dangerous skin cancer. Histone modifiers usually become dysregulated during the process of carcinoma development, thus there is potential for a histone modifier inhibitor as a useful drug for cancer therapy. There is a multitude of evidence regarding the role of G9a, a histone methyltransferase (HMTase), in tumorigenesis. In this study, we first showed that G9a was significantly upregulated in melanoma patients. Using the TCGA database, we found a significantly higher expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…In addition, CM-272 is a potent dual inhibitor of G9a (a type of histone methyltransferase) and DNMTs for the treatment of hematological malignancies [ 119 ]. G9a is responsible for methylating lysine 9 of histone 3 (H3K9), and overexpression of G9a leads to increased tumor progression in some tumors [ 120 , 121 ]. It is involved in the transcriptional repression of the tumor suppressor gene PTEN , and upregulation of the G9a gene and downregulation of the PTEN gene can predict poor overall survival [ 122 ].…”
Section: Targeting Dnmtsmentioning
confidence: 99%
“…In addition, CM-272 is a potent dual inhibitor of G9a (a type of histone methyltransferase) and DNMTs for the treatment of hematological malignancies [ 119 ]. G9a is responsible for methylating lysine 9 of histone 3 (H3K9), and overexpression of G9a leads to increased tumor progression in some tumors [ 120 , 121 ]. It is involved in the transcriptional repression of the tumor suppressor gene PTEN , and upregulation of the G9a gene and downregulation of the PTEN gene can predict poor overall survival [ 122 ].…”
Section: Targeting Dnmtsmentioning
confidence: 99%
“…It has been observed that the expression of G9a is upregulated in a number of cancers, including aggressive lung cancer, multiple myeloma, aggressive ovarian carcinoma, brain cancer, hepatocellular carcinoma, esophageal squamous cell carcinoma, and malignant melanoma (Wozniak et al, 2007;Gao et al, 2013;Hua et al, 2014;Lehnertz et al, 2014;Hu et al, 2019;Dang et al, 2020). Higher G9a expression levels have often been associated with poor prognosis (Chen et al, 2010;Ke et al, 2014;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, G9a inhibition downregulated HES1 in both protein level and TF activity in GSC, which has been reported to promote EMT and cell migration [90]. The underlying regulation can be explained by the function of G9a as a coactivator, since it has been reported that G9a activates the Notch signaling pathway by regulating Notch1 and Hes1 in cancer progression of melanoma[91]. Another possibility is that G9a might promote AKT activity which in turn upregulates HES1[61, 92].…”
Section: Discussionmentioning
confidence: 99%